2009
DOI: 10.1158/1940-6207.capr-08-0103
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of Colorectal Neoplasia by Estrogen: Potential Role of Vitamin D Activity

Abstract: Postmenopausal hormone replacement therapy lowers colon cancer incidence. In humans, the mechanism is unknown, but animal models suggest that it may involve activation of the vitamin D receptor (VDR) pathway.The aims of our study were to determine whether estrogen intervention affects global gene expression in rectal mucosal biopsies and whether vitamin D-related genes are affected.Estradiol was given to raise serum estradiol to premenopausal levels in 10 postmenopausal women under close nutritional control. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 31 publications
2
37
0
Order By: Relevance
“…Flexible sigmoidoscopies were performed after a 60-mL tap water enema between 0800 and 1000. Rectosigmoid mucosal biopsy specimens were taken w15 cm from the anal verge as described previously (15,16). Six biopsy specimens for gene expression analysis were taken, immediately frozen in liquid nitrogen, and stored at 2808C.…”
Section: Procedures and Sample Collectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flexible sigmoidoscopies were performed after a 60-mL tap water enema between 0800 and 1000. Rectosigmoid mucosal biopsy specimens were taken w15 cm from the anal verge as described previously (15,16). Six biopsy specimens for gene expression analysis were taken, immediately frozen in liquid nitrogen, and stored at 2808C.…”
Section: Procedures and Sample Collectionsmentioning
confidence: 99%
“…Our group has completed several studies of molecular events in rectosigmoid mucosal biopsy specimens that accompany administration of putative risk reduction agents such as estrogen and folic acid (15,16). The present study aimed to identify the effects of calcium and/or 1,25-dihydroxyvitamin D 3 [1,25 (OH) 2 D 3 ] supplementation on gene expression profiles of the human colorectal mucosa of subjects at moderate risk of CRC consuming a Western-style diet (WD).…”
Section: Introductionmentioning
confidence: 99%
“…Additional data suggest that this action may, at least in part, be mediated through VDR signaling. RT-PCR results confirmed that estrogen administration increased mRNA expression of VDR as well as of a downstream target of vitamin D action, E-cadherin [140]. Besides HRT, high estrogen content of soy is implicated to be…”
Section: Estrogen Pathway In Crc: Interaction With Vitamin Dmentioning
confidence: 61%
“…When mice were fed a diet containing soy, the expression of the synthesizing vitamin D hydroxylase, CYP27B1, was enhanced, and that of the catabolic hydroxylase, CYP24A1, was decreased [50]. In a clinical pilot trial [140], postmenopausal women with a past history of rectal adenomas were given a daily dose of 17 β-estradiol for 1 month to reach premenopausal hormone levels. Rectal biopsies were obtained at the beginning and end of the trial.…”
Section: Estrogen Pathway In Crc: Interaction With Vitamin Dmentioning
confidence: 99%
“…Risk factors include alcohol (11,12), red meat consumption (11,(13)(14)(15)(16), low vegetable and folate intake (17,18), smoking (19)(20)(21), sedentary lifestyle, overweight, obesity (22)(23)(24), diabetes (25) and short duration and poor quality of sleep (26); protective factors include fish consumption (14,15), hormone replacement therapy (27,28), oral contraceptive use (29), calcium intake (30), higher bone mass levels (31) and physical exercise (11,(32)(33)(34). The results from several epidemiological studies are inconsistent concerning the effects of dietary fiber intake (35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%